2012
DOI: 10.1136/flgastro-2011-100065
|View full text |Cite
|
Sign up to set email alerts
|

The future of gastroenterology training: instruction in technical skills

Abstract: Endoscopy training has developed extensively over the past decade but despite signifi cant improvements many challenges remain and further development of endoscopy training programmes and content is required. Endoscopy training is struggling with increasing pressure from service provision and competition for limited National Health Service (NHS) resources. There is a rapidly increasing proportion of work shifting from diagnostic to therapeutic practice in the face of limited dedicated therapeutic training prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that regular feedback, particularly in regard to the adenoma detection rate, can in itself improve performance 35 36 . The importance of non-technical skills alongside those targeting technical performance metrics is being increasingly acknowledged 37 . Whereas all endoscopists would acknowledge the importance of technical proficiency, the relevance of non-technical skills such as communication in a highly skilled examination is likely to be less well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that regular feedback, particularly in regard to the adenoma detection rate, can in itself improve performance 35 36 . The importance of non-technical skills alongside those targeting technical performance metrics is being increasingly acknowledged 37 . Whereas all endoscopists would acknowledge the importance of technical proficiency, the relevance of non-technical skills such as communication in a highly skilled examination is likely to be less well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore paramount that these NTS are taught and developed in staff. There is a growing body of opinion that NTS are the most important aspect of medical practice and NTS competence should be integral to training in endoscopy 5 7 9 13…”
Section: Why Are Nts Important In Endoscopy?mentioning
confidence: 99%
“…NTS training has received increasing recognition in other areas of healthcare such as surgery, anaesthetics and emergency medicine, but there has been little investment in team training and development in endoscopy to date 5. There is, however, growing momentum for teaching NTS as well as, or alongside technical skills, particularly with the development of the national BCSP and advancing therapeutic endoscopy 5 9…”
Section: Nts Training In Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Trainers may feel most comfortable providing feedback on technical skills, yet the teaching of nontechnical skills is equally important. 4 In this commentary, we aim to stimulate discussion of feedback among endoscopy teachers and to make practical suggestions for providing effective feedback to endoscopy learners. This commentary is not based on a systematic review of the literature, but rather on our experiences as endoscopy teachers and education researchers and scholars, and on insights from the American Society for Gastrointestinal Endoscopy's Train the Trainers course.…”
mentioning
confidence: 99%